Impact of Global Changes on Mountains: Responses and Adaptation - Grover, Velma I; Borsdorf, Axel; Breuste, Jörgen; Tiwari, Prakash Chandra; Frangetto, Flavia Witkowski (CRC Press, 2015)
Mountain regions encompass nearly 24 percent of the total land surface of the earth and are home to approximately 12 percent of the world's population. Their ecosystems play a critical role in sustaining human life both in the highlands and the lowlands. During recent years, resource use in high mountain areas has changed mainly in response to the